2002
DOI: 10.1002/sim.1225
|View full text |Cite
|
Sign up to set email alerts
|

Penalized likelihood approach to estimate a smooth mean curve on longitudinal data

Abstract: This paper aims to propose a penalized likelihood approach to estimate a smooth mean curve for the evolution with time of a Gaussian variable taking into account the correlation structure of longitudinal data. The model is an extension of the mixed effects linear model including an unspecified function of time f(t). The estimator (circumflex)f(t) is defined as the solution of the maximization of the penalized likelihood and is approximated on a basis of cubic M-spline with a reduced number of knots. We present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…When is fixed, pl is maximized by using an approximation off (t) on a basis of cubic M-splines with a limited number K of knots [18]. Typically, K is between 5 and 20.…”
Section: Cubic-spline Approximationmentioning
confidence: 99%
See 3 more Smart Citations
“…When is fixed, pl is maximized by using an approximation off (t) on a basis of cubic M-splines with a limited number K of knots [18]. Typically, K is between 5 and 20.…”
Section: Cubic-spline Approximationmentioning
confidence: 99%
“…The non-parametric alternative defines the estimator of the function f (t) as the solution of the maximization of the penalized log-likelihood which leads to a natural cubic-spline estimator forf (t) with one knot for each distinct time of measurement [15--17]. As the latter is computationally prohibitive when the number of distinct time points is large, an hybrid approach has emerged where a moderate number of knots is used (5 to 20 in most cases) and parameters are estimated using penalized likelihood [13,18,19]. This approach is computationally tractable and remains non-parametric in spirit as the number of knots must be large enough so that penalized likelihood estimations are unchanged when the number of knots increases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, polynomial methods are widely used in longitudinal modeling, and spline methods have been previously used in latent class time series analysis (Winsberg and De Soete, 1999) and in mixed effects longitudinal analysis (Jacqmin-Gadda, 2002). For regression models it has been shown that penalized least squares estimation with (2) is equivalent to fitting the trajectories with a basis of cubic splines (Wahba 1990).…”
Section: Performance For Trajectory Estimationmentioning
confidence: 99%